Disodium Phosphate: A Highly Efficient Catalyst for One-Pot Synthesis of Substituted 3,4-Dihydropyrano[3,2-C]Chromenes - Shitole, Balasaheb V.; Shitole, Nana V.; Kakde, Gopal K. (Orbital: The Electronic Journal of Chemistry, 2017)
Disodium phosphate catalyzed one-pot synthesis of 3,4-dihydropyrano[3,2-c]chromenes, from aldehydes, active methylene compounds malononitrile and 4-hydroxycoumarin in ethanol:water (1:1) under reflux temperature. The attractive features of this process are inexpensive, efficient, as well as user friendly. DOI: http://dx.doi.org/10.17807/orbital.v9i3.896